Investigating the Interplay of Foreign Language Enjoyment, Elaboration Strategies, Gender Differences, and Academic Achievement among Chinese EFL learners - Jiang, Meihong (International Journal of Linguistics and Translation Studies, 2023)
The objective of this study was to investigate whether foreign language enjoyment predicted elaboration strategy and academic achievement and to test whether there are gender differences in the relations of foreign language enjoyment, elaboration strategies, and academic achievement in the English as a foreign language (EFL) context in China. Data were collected from 536 Chinese secondary EFL learners aged 11-15 years in Grade 7 and Grade 8. Results from structural equation modeling analysis (SEM) found that foreign language enjoyment was positively correlated with EFL learning achievement directly and indirectly, mediated by elaboration strategies. In addition, results of multi-group analysis showed that indirect relations from foreign language enjoyment to EFL learning achievement were not moderated by gender, indicating that the model of “foreign language enjoyment→elaboration strategies→EFL learning achievement” was invariant across genders. These findings add to the literature on the mechanism linking foreign language enjoyment and EFL learning achievement and an increasing number of studies concerning the female dominance in terms of language learning. Implications, limitations, and directions for future research are discussed.